2008
DOI: 10.1080/02770900802126958
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of IgE as Biomarker in Asthma

Abstract: Serum IgE level was predictive in asthma, and it may be used to differentiate between asthmatic and non-asthmatic individuals in conjunction with other biomarkers. Specific immunotherapy reduced serum total IgE level in 36% of patients with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…IgE is also one among the main factors constituting with FcεR I on the surfaces of the mast cells causing release of chemokines and cytokines by degranulation, resulting in severe asthmatic condition (Calabrese, Triggiani, Marone, & Mazzarella, ; Galli et al, ). Elevated levels of IgE (tenfolds) were reported in the blood of asthma patients when compared with normal healthy adult, indicating the significant presence of IgE during asthmatic conditions (Ahmad Al Obaidi, Mohamed Al Samarai, Yahya Al Samarai, & Al Janabi, ; Sandeep et al, ). However, the true factor for the involvement of IgE in causing asthma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…IgE is also one among the main factors constituting with FcεR I on the surfaces of the mast cells causing release of chemokines and cytokines by degranulation, resulting in severe asthmatic condition (Calabrese, Triggiani, Marone, & Mazzarella, ; Galli et al, ). Elevated levels of IgE (tenfolds) were reported in the blood of asthma patients when compared with normal healthy adult, indicating the significant presence of IgE during asthmatic conditions (Ahmad Al Obaidi, Mohamed Al Samarai, Yahya Al Samarai, & Al Janabi, ; Sandeep et al, ). However, the true factor for the involvement of IgE in causing asthma remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We included in our analysis proportion of Native American ancestry (ranging from 0 to 1) for Study A (20), proportion of African ancestry (ranging from 0 to 1) (19), body mass index (BMI) category (22), socioeconomic status (23), total immunoglobulin E (IgE) levels (24,25), family history of asthma (26), chest illnesses before age 2 (27), maternal prenatal smoking (28), birth weight (28,29), recruitment center (representative of geographic location) (30) and sex (21). …”
Section: Methodsmentioning
confidence: 99%
“…However, only a subset of allergic patients develops asthma and, in contrast, substantial numbers of nonatopic subjects have asthma. Conversely, some authors reported an inverse association between serum IgE and FEV1 values in asthma [138], possibly in relation to the increased severity of nonatopic asthma. Although the importance of IgE for clinicians taking care of asthmatics had progressively declined, the arrival of anti-IgE therapy reversed this trend after the demonstration of its efficacy in allergic asthma, including at the severe side of the spectrum [1].…”
Section: Ige As a Therapeutic Target And A Biomarker In Asthmamentioning
confidence: 99%